Answer:
[tex] \underline{\boxed{Part \: A}}: \\ \: \\the \: function \: is \: a \: \boxed{ geometric \: sequence} \\ \\ \underline{\boxed{Part \: B}}: \\\boxed{T_n = a( {r})^{(n - 1)}} \\ \\ \underline{\boxed{Part \: C}}: \\ \boxed{T_4 = T_3( { - 3})^{(1)}} \\ \\ \underline{\boxed{Part \: D}}: \\ \boxed{ T_9 = 26,244}[/tex]
Step-by-step explanation:
[tex] \underline{\boxed{Part \: A}}: \\ \: \\the \: function \: is \: a \: \boxed{ geometric \: sequence} \\ this \: due \: to \: their \: common \: ratio (r)= \boxed{- 3} \\ \\ \underline{\boxed{Part \: B}}: \\ \\ let \: the \: required \: term \: be \to \: T_n \\ let \: the \: first \: term \: be \to \: a \\ let \: the \:common \: ratio \: be \to \: r \\ hence : \boxed{T_n = a( {r})^{(n - 1)}} \\ where \: n \: is \: the \: number \: of \: term. \\ \\ \underline{\boxed{Part \: C}}: \\ let \: the \: required \: term \: be \to \: T_4 \\ hence : \boxed{T_4 = T_3( { - 3})^{(1)}} \\ \\ \underline{\boxed{Part \: D}}: \\if \: a = 4 : r = ( - 3) : n = 9 \\ hence : \boxed{T_9 = 4( { - 3})^{(9 - 1)}} \\ hence : \boxed{T_9 = 4( { - 3})^{(8)}} \\T_9 = 4( 6,561) \\ \boxed{ T_9 = 26,244}[/tex]